Urban Atmospheres - Niels Albertsen (Ambiances)
Gernot Böhme proposes the concept of atmosphere as the basic concept of a new aesthetics without a point of departure in art. This article speculates on some possible urban implications of this concept. To start with, I present various ontological and epistemological aspects of the concept and specify some atmospheric dimensions of art and architecture. Then, I discuss Georg Simmel’s concept of landscape, which seems to refuse the presence of atmosphere in the metropolis, as an overture to the next section on urban atmospheres. Urban atmospheres are multi-sensorial and demonstrate considerable variation from densely built inner-city areas to the modern spaces of urban sprawl. Mobility is a significant factor in relation to modern urban regions, the atmosphere of which might be thought of as a picturesque landscape for cyborgs. Urban communities may be of a primarily atmospheric kind. The historical city may have an atmosphere of age that can be sensed without much historical knowledge, and atmosphere may be the source of urban political struggle. Finally, I examine the atmospheres of the urban center and the urban region with a focus on Dag Østerberg’s recent work on Oslo, arguing that atmospheric aspects of the socio-material action fields within the urban region may modify Østerberg’s conclusions regarding the imaginary status of the center and the urban identity of the region. The pivotal argument of the article is that atmosphere is an important but overlooked dimension of both human relations in urban environments and the relationship between the human and the built environment.